Arahan Pengembangan Transportasi Sungai Sebagai Transportasi Alternatif Angkutan di Kota Makassar - Indira Satriani Nursalam; Muhammad Yamin Jinca; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2018)
The increasing number of vehicles and transportation needs that are not accompanied by the development of transportation infrastructure result in transportation problems which one of them is congestion. The city of Makassar as one of the metropolitan cities with similar transportation problems needs to develop another alternative transportation system for example, river or water transportation. This study aims to measure the feasibility of the Tallo River as a river or water transportation route, and to formulate guidance for the development of river transportation as alternative transportation system in the city of Makassar. Data collection methods used were observation, interviews, documentation, and literature studies. The analytical methods used are quantitative analysis, spatial analysis and SWOT analysis. The results of this study indicate that the Tallo River is feasible to be used as a river transportation route based on four of the five feasibility aspects, which are, river boundaries, river depth, river width, and barrier-free space. Meanwhile, the guidance of its development is to develop the entire potential of the Tallo River in accordance with the directions of the Makassar City Spatial Plan, increasing investment in transportation revitalization, and developing river transportation that supports tourism.